2019
DOI: 10.5194/soil-5-49-2019
|View full text |Cite
|
Sign up to set email alerts
|

Application of a laser-based spectrometer for continuous in situ measurements of stable isotopes of soil CO<sub>2</sub> in calcareous and acidic soils

Abstract: Abstract. The short-term dynamics of carbon and water fluxes across the soil–plant–atmosphere continuum are still not fully understood. One important constraint is the lack of methodologies that enable simultaneous measurements of soil CO2 concentration and respective isotopic composition at a high temporal resolution for longer periods of time. δ13C of soil CO2 can be used to derive information on the origin and physiological history of carbon, and δ18O in soil CO2 aids in inferring the interaction between CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…High belowground allocation helps explain the high rate of SOC (soil organic carbon) accumulation observed over the period since afforestation (Grünzweig et al, 2007;Qubaja et al, 2019). Note that, irrespective of the soil carbon accumulation, the abiotic component to the CO 2 flux seems to be significant in dry environments (Table 3) and in particular in the dry seasons, when biological activities drastically decrease (Kowalski et al, 2008;Lopez-Ballesteros et al, 2017;Serrano-Ortiz et al, 2010;Martí-Roura et al, 2019). The results show that considering the abiotic effects on estimating soil respiration and, in turn, on estimating the carbon budget in dry calcareous soils can play an important part in estimating soil and ecosystem respiration fluxes (Angert et al, 2015;Roland et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…High belowground allocation helps explain the high rate of SOC (soil organic carbon) accumulation observed over the period since afforestation (Grünzweig et al, 2007;Qubaja et al, 2019). Note that, irrespective of the soil carbon accumulation, the abiotic component to the CO 2 flux seems to be significant in dry environments (Table 3) and in particular in the dry seasons, when biological activities drastically decrease (Kowalski et al, 2008;Lopez-Ballesteros et al, 2017;Serrano-Ortiz et al, 2010;Martí-Roura et al, 2019). The results show that considering the abiotic effects on estimating soil respiration and, in turn, on estimating the carbon budget in dry calcareous soils can play an important part in estimating soil and ecosystem respiration fluxes (Angert et al, 2015;Roland et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…16,[37][38][39] OA-ICOS techniques have drawn broad interest due to their simple structures and high sensitivities. 1,7,36,[38][39][40][41] Jost et al designed the rst OA-ICOS instrument for determining 13 C/ 12 C and 18 O/ 16 O ratios from CO 2 rotation/vibration ne structures at three different combined bands. Their preliminary results showed that the accuracy of d 13 C and d 18 O at 0.8 Hz is 3.3& and 2.8&, respectively, and the measurements were conducted over a period of 10 hours for pure CO 2 gas samples at 26 h Pa. By averaging 100 spectra over a subset of the data, they achieved an accuracy of 1.6& for d 13 C and 0.8& for d 18 O.…”
Section: Laser Spectroscopy Theorymentioning
confidence: 99%
“…The optimal accuracy of d 13 C analysis is 0.022& by averaging the data obtained over 256 seconds, and the highest accuracy for d 18 O analysis is ±0.077& at the same time interval. 7 2.2.4. Quantum cascade laser absorption spectrometer (QCLAS).…”
Section: Laser Spectroscopy Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Non-destructive approaches employing compound-specific labels (e.g., 13 C/ 15 N-labeled organic compounds) coupled to trace-gas analysis have a long history of use in soil biogeochemistry and microbiology ( Stevens et al, 1993 ; Staddon, 2004 ). The use of natural-abundance isotope, isotopologue, and isotopomer measurements on gaseous fluxes of CO 2 , CH 4 , or N 2 O also provide detailed analysis of potential microbial pathways leading to the transformation and release of those gases ( Wankel et al, 2017 ; Joseph et al, 2019 ). However, coupling soil processes, as informed by trace gas measurements (e.g., respiration, decomposition, denitrification), with the metabolisms underpinning the process remains reliant on destructive approaches.…”
Section: Development and Implementation Of Novel Toolsmentioning
confidence: 99%